2019
DOI: 10.1108/ecam-02-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

Green and sustainable practices in the construction industry

Abstract: Purpose The purpose of this paper is to differentiate between sustainable and green construction and significantly contribute to empirical investigations related to the impact of green construction factors on sustainable performance and to test the theory of planned behavior in the construction context and empirically assess green construction factors and the performance model. The model incorporates green construction factors that link construction activities with suppliers and customers to support environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 87 publications
(91 reference statements)
4
80
1
1
Order By: Relevance
“…Both studies found no evidence of the moderating effect of green practice advantages (GPAs). In contrast, RA was found to strengthen the relationship between GPs and the sustainable performance of construction companies (Shurrab et al, 2019). In manufacturing firms, GPAs were found to moderate the effects of stakeholder pressure on environmental management and accounting implementation (Wang, Wang, & Wang, 2019).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Both studies found no evidence of the moderating effect of green practice advantages (GPAs). In contrast, RA was found to strengthen the relationship between GPs and the sustainable performance of construction companies (Shurrab et al, 2019). In manufacturing firms, GPAs were found to moderate the effects of stakeholder pressure on environmental management and accounting implementation (Wang, Wang, & Wang, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…For example, in Japan where environmental management practices are rigorously monitored, car manufacturers enjoy a higher RA worldwide than those from the United States (Narasimhan & Schoenherr, 2012). In contrast with Ferrón-Vílchez (2016), Choi and Han (2019) and Shurrab et al (2019), which focused on one specific advantage of GPs or considered the advantages of GPs as a single or general construct, the aforementioned discussion indicates that there are various advantages of GPs with a heterogenous influence on EnvP. Furthering the above discussion, the present study argues that the moderating effects of various GPAs and the degree of GPAs are diverse.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations